Rapid and Controlled: Microflow Reactor-Assisted Synthesis of Cinnamaldehyde and Ethyl Cinnamate along with Their Cytotoxic Activity Against Several Cell Lines - Nindita Fransiska Rahmawati; Muhtadi Muhtadi; Andi Suhendi; Ahmad Fauzi; Didin Mujahidin; Ahwan Ahwan; Agustono Wibowo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Cinnamaldehyde is a major aromatic compound utilized in the pharmaceutical industry due to its diverse biological activities, including anticancer potential. This study aims to develop a rapid and controlled synthesis method for cinnamaldehyde and ethyl cinnamate using microflow reactor technology, followed by structural elucidation and cytotoxic evaluation against HeLa, MCF-7, and T47D cancer cell lines. The synthesis of cinnamaldehyde was performed via aldol condensation of benzaldehyde and acetaldehyde (1.3:1 molar ratio) at 70°C, while ethyl cinnamate was synthesized through a two-step process involving Pinnick oxidation and Fischer esterification. The results demonstrated that microflow synthesis achieved a cinnamaldehyde yield of 52% with high purity (100% based on HPLC relative area), and ethyl cinnamate with 99% purity. In cytotoxic assays, synthesized cinnamaldehyde exhibited moderate activity, most notably against HeLa cells with an IC₅₀ of 95 µg/mL, whereas ethyl cinnamate showed lower potency (IC₅₀ > 200 µg/mL). Although the synthesized compounds were less potent than the standard cinnamaldehyde (IC₅₀ 1.56 µg/mL) and Doxorubicin control, this study confirms that microflow reactor technology is a highly effective and time-efficient method for producing high-purity cinnamate derivatives.